STRATEGI KOMUNIKASI ANTARPRIBADI PASANGAN SUAMI DAN ISTRI DALAM MENCEGAH TINDAKAN PERSELINGKUHAN DI KABUPATEN DONGGALA - Sumarni Zainuddin; Muhammad Wahid (Kinesik, 2022)
Marriage is an expression of the peak of a relationship in which there are various kinds of rules that certainly cannot be broken, especially concerning infidelity. The purpose of the study was to determine the interpersonal communication strategy of husband and wife in preventing infidelity in Donggala Regency. Qualitative research method. Informants were taken by purposive sampling technique. This study uses observation and in-depth interviews. The results showed that in preventing acts of infidelity, interpersonal communication strategies that must be applied by husband and wife couples in Donggala Regency are mutual respect, maintaining commitments that have been mutually agreed upon, being open to each other in information, applying polite and courteous attitudes towards partners. , maintain the sense of trust given by the partner, and the most important thing is to be able to control yourself well when using social media that can connect with anyone, both near and far.